A tool to assess potential for alien plant establishment and expansion under climate change. (15th August 2015) - Roger, Erin; Duursma, Daisy Englert; Downey, Paul O.; Gallagher, Rachael V.; Hughes, Lesley; Steel, Jackie; Johnson, Stephen B.; Leishman, Michelle R.
Abstract: Predicting the influence of climate change on the potential distribution of naturalised alien plant species is an important and challenging task. While prioritisation of management actions for alien plants under current climatic conditions has been widely adopted, very few systems explicitly incorporate the potential of future changes in climate conditions to influence the distribution of alien plant species. Here, we develop an Australia-wide screening tool to assess the potential of naturalised alien plants to establish and spread under both current and future climatic conditions. The screening tool developed uses five spatially explicit criteria to establish the likelihood of alien plant population establishment and expansion under baseline climate conditions and future climates for the decades 2035 and 2065. Alien plants are then given a threat rating according to current and future threat to enable natural resource managers to focus on those species that pose the largest potential threat now and in the future. To demonstrate the screening tool, we present results for a representative sample of approximately 10% (n = 292) of Australia's known, naturalised alien plant species. Overall, most alien plant species showed decreases in area of habitat suitability under future conditions compared to current conditions and therefore the threat rating of most alien plant species declined between current and future conditions. Use of the screening tool is intended to assist natural resource managers in assessing the threat of alien plant establishment and spread under current and future conditions and thus prioritise detailed weed risk assessments for those species that pose the greatest threat. The screening tool is associated with a searchable database for all 292 alien plant species across a range of spatial scales, available through an interactive web-based portal athttp://weedfutures.net/ . Highlights: We develop a tool to assess threat of alien plants spreading under climate change. The screening tool uses five spatially explicit criteria to establish a threat rating. Most alien plant species modelled declined between current and future conditions. Management can use the tool to prioritise high risk species for eradication. Results can be queried through a web-based portal athttp://weedfutures.net/ .